2016
DOI: 10.1097/hjh.0000000000000945
|View full text |Cite
|
Sign up to set email alerts
|

Brunei epidemiological stroke study

Abstract: The prevalence of hypertension in Brunei is high in both women and men. Information campaigns and prevention programs are needed to be able to cope with the increasing problem of hypertension and resulting diseases like stroke in Brunei in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…When comparing neighboring countries, Brunei (48.3%), Indonesia (33.4%), and Malaysia (35.3%) have higher prevalence of hypertension than Cambodia ( Lupat et al, 2016 ; Peltzer and Pengpid, 2018 ; Ab Majid et al, 2018 ), whereas a lower prevalence were reported in Vietnam (25%) ( Son et al, 2012 ). Higher prevalence of hypertension in men than women has been also reported in Myanmar (31% for males versus 29% for females) ( Bjertness et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…When comparing neighboring countries, Brunei (48.3%), Indonesia (33.4%), and Malaysia (35.3%) have higher prevalence of hypertension than Cambodia ( Lupat et al, 2016 ; Peltzer and Pengpid, 2018 ; Ab Majid et al, 2018 ), whereas a lower prevalence were reported in Vietnam (25%) ( Son et al, 2012 ). Higher prevalence of hypertension in men than women has been also reported in Myanmar (31% for males versus 29% for females) ( Bjertness et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%